Optimizing Company Performance Through Industrial Coordinator Training : A Practical Needs Assessment - Putri Nia Luki Patmasari Putri; Muhamad Abdul Jumali; Rusdiyantoro rusdiyantoro (UNIPA PRESS, 2023)
The study of performance is incredibly fascinating. One of them is the way in which mid-level management functions as both a conduit for information to top management and the person in control of subordinates. This study aims to enhance the coordinator of the industrial department's performance. This study's data processing and analysis procedure employs a qualitative approach by carrying out an analysis using the TNA (Training Need Analysis) method. At electromotor engine repair service firms in East Java, this method is used to assess the variables that contribute to delays in the completion of repairs of goods as well as the kind of training provided to coordinators to prevent delays in the completion of repairs of goods. The outcomes show in the study, it was discovered that the absence of effective communication between division coordinators in the industrial department, skill gaps, and workers who are not suited for the job are the main causes of delays in the completion of goods. Because the percentage is still low for corporate performance and still less productive, the performance value in each division, such as industrial repair, is 6.1%, vacuum pump 6.6%, blower 6.2%, fabrication 7.4 and rewinding 7.5% to complete the items.